Legal Analysis of the Police Intelligence Function in Early Detection of Inter-Village Brawls: A Socio-Legal Approach to the Effectiveness of Social Conflict Prevention - Agus Jaelani; Harmono Harmono (Ann Publisher, 2026)
Background. The phenomenon of inter-village brawls shows that social conflicts at the local level no longer arise spontaneously, but develop through more complex and unpredictable processes. In this context, early detection is becoming increasingly important as an effort to read potential conflicts before they develop into open violence. Aims. This research aims to examine how the police intelligence function is carried out in detecting potential conflicts between villages, how the basis of its authority is constructed within the applicable legal framework, and the extent of its effectiveness in preventing the escalation of social conflicts. Methods. This study uses a socio-legal approach, combining normative analysis of laws and regulations with empirical data obtained through interviews in the Cirebon Regency area. Result. The results show that, in practice, early detection occurs more through informal social mechanisms, such as interaction with the community and readings of local dynamics, than through structured systems. However, this role often stops at the identification stage because there is no clarity on the limits of authority for carrying out preventive actions and no system to integrate information and policy responses. These findings confirm that early detection cannot be understood solely as a technical mechanism for information collection, but rather as a social process that is interpretive and contextual. Conclusion. Therefore, its effectiveness is determined not only by the availability of information but also by the system's ability to interpret and follow up on it in a coordinated manner. Implementation. This research offers a new perspective by placing early detection as a meeting space between social practice, legal construction, and institutional capacity in the prevention of social conflict.